The Influence Of The Blended Learning Model On Bahasa Indonesia Learning Outcomes Of Class IV Students Of SDN No. 21 Tangnga-Tangnga Kabupaten Bantaeng - Rifaldi, Achmad; Nurhaedah, Nurhaedah; Irfan, Muhammad (International Journal of Elementary School Teacher, 2023)
This research aims to determine the description of student learning outcomes in Indonesian language learning for class IV students at SDN 21 Tangnga-Tangnga and to determine the effect of implementing the blended learning model on Indonesian language learning outcomes for class IV students at SDN 21 Tangnga-Tangnga. This type of research is a quasi-experiment which shows the influence of variable This research uses Nonequivalent Control Group Design as the research design. The instrument used in this research was a learning outcomes test given to students in both classes. The data analysis used is Normality Test, Homogeneity Test, and Hypothesis Test. Hypothesis testing was carried out using paired samples T-Test. The results showed that the pre-test scores for the two classes had no difference, namely 58.50. The average difference obtained in the post-test score for the experimental class was 80.00, higher than the control class with an average post-test score of 74.83. Based on the results of the hypothesis test, it is known that the probability value obtained is smaller than 0.05. So, it can be concluded that there is an influence of the application of the blended learning model on Indonesian language learning outcomes at SDN No. 21 Tangnga-Tangnga Bantaeng.